IMPLEMENTASI AKUNTANSI DAN KESESUAIANNYA DENGAN STANDAR AKUNTANSI KEUANGAN (SAK-EMKM) PADA USAHA BUDIDAYA IKAN LELE - Siti Fitriah Nur Saadah; Nilasari, Yekti; Permana, Indra Surya (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2024)
Micro, small, and medium enterprises (MSMEs) play an important role in meeting the needs of society, creating jobs, and increasing foreign exchange earnings. However, the lack of understanding of how to prepare financial statements in accordance with accounting standards makes MSMEs less aware of the benefits of financial statements. This study aims to implement and determine the results of the implementation of accounting and its compliance with the SAK EMKM in catfish farming businesses. A descriptive method with a qualitative approach was used in this study. Data was collected through interviews and observations, using primary and secondary data. The results of the study showed that catfish farming businesses have simple records only regarding income and expenses. After the implementation of the study, financial statements based on SAK EMKM, including transaction lists, general journals, ledgers, trial balances, balance sheets, and income statements, were proven to be implemented well.